Bibliometric analysis of the body posture in relation to visual display terminals (VDTs). - García-Remeseiro, Tania; Gutiérrez-Sánchez, Águeda (Work, 2019)
BACKGROUND: In modern society, there is an increase both in the demand and the duration of computer work. Failure to correct body posture while using the computer has become a serious health hazard. OBJECTIVE: To identify global trends in research related to body posture and visual display terminals (VDTs) using a bibliometric approach. METHODS: In the search process, the keywords (posture *) AND (computer* OR "visual display terminal") were used in the study title section, in the Wos, Scopus and Medline databases. RESULTS: 149 references published between 1970 and 2016 were analyzed. The studied variables were the years of publication, authorship and collaboration index, publication type, titles of journals, most used languages, impact of the publications, as well as content of the articles. CONCLUSIONS: In recent years, the studies on body posture in relation to VDT have been increased both in quantity and quality of publications. The analysis and/or design of the workplace, as well as the elements that make up the computer (keyboard and mouse) are the most researched topics in the area.